002 A randomised study of temporary epicardial cardiac resynchronisation vs conventional right ventricular pacing in cardiac surgical patients. (16th May 2012) - Russell, S J; Tan, C; Ashraf, S; Zaidi, A; O'Keefe, P; Fraser, A G; Yousef, Z R
Abstract : Introduction: Left ventricular (LV) function is an important indicator of morbidity and mortality after cardiac surgery. Therefore, interventions to optimise peri-operative LV function may improve surgical outcomes. Biventricular (BiV) pacing has been shown to improve haemodynamic function in heart failure patients and temporary BiV pacing is feasible after cardiac surgery. Therefore, temporary BiV pacing may be beneficial to heart failure patients after cardiac surgery. Aim: The aim of this trial was to investigate the clinical utility of temporary BiV pacing delivered via epicardial wires attached to the right atrium (RA), right ventricle (RV) and left ventricle (LV) after cardiac surgery. Methods: 55 subjects undergoing elective cardiac surgery (coronary artery bypass grafting and/or valve surgery) were recruited from two cardiac centres, over an 18-month period commencing January 2010. 38 subjects completed the protocol. Nine subjects were removed at the operators request including: "off pump" bypass surgery, patient referred for alternative mode of revascularisation or surgical "turn down". 19 subjects were randomly assigned to receive temporary (BiV) pacing using a dedicated triple chamber temporary pacing box with the capacity to programme the atrio-ventricular (AV) and inter-ventricular (VV) intervals. 19 received "standard pacing" after cardiac surgery. The duration of level 3 care was measured for each subject. In brief, this is the requirement for either invasive ventilation, multi-organ support or haemodynamic support with more than one inotrope/vasocontrictor or intra-aortic balloon pump. The trial was powered to compare the primary endpoint of transition from level 3 to level 2 care in the two groups. Secondary endpoints included acute haemodynamic performance in different pacing modes: immediately after the operation, 6 h, 18 h and 24 h after admission to cardiac intensive care. The pacing modes assessed included: atrial inhibited (AAI); ventricular inhibited (VVI-RV); dual chamber (DDD-RV); biventricular (DDD-BiV) and left ventricular pacing (DDD-LV). Base rate for pacing was set at 86/min and continued for the duration of level 3 care. The haemodynamic data were measured using a pulmonary arterial catheter using either thermodilution or continuous cardiac output measurements. Results: The baseline demographics are illustrated in Abstract 002 table 1 . The acute haemodynamic measurements at 18 h, Abstract 002 table 2 . Conclusions: BiV pacing significantly improved haemodynamics in the early part of the post-operative period compared to standard AAI pacing at 18 h. There is a suggestion that the improvement in haemodynamic function may translate into clinical benefit. The duration of level 3 care was 57.1 h in the standard pacing group compared to 44.5 h in the BiV group. However, the 22% reduction in level 3 care in the BiV group compared to the standard pacing group did not reach statistical significance.